Representations of Pitch and Timbre Variation in Human Auditory Cortex - Allen, Emily J; Burton, Philip C; Olman, Cheryl A; Oxenham, Andrew J (The Journal of neuroscience, 2017)
Pitch and timbre are two primary dimensions of auditory perception, but how they are represented in the human brain remains a matter of contention. Some animal studies of auditory cortical processing have suggested modular processing, with different brain regions preferentially coding for pitch or timbre, whereas other studies have suggested a distributed code for different attributes across the same population of neurons. This study tested whether variations in pitch and timbre elicit activity in distinct regions of the human temporal lobes. Listeners were presented with sequences of sounds that varied in either fundamental frequency (eliciting changes in pitch) or spectral centroid (eliciting changes in brightness, an important attribute of timbre), with the degree of pitch or timbre variation in each sequence parametrically manipulated. The BOLD responses from auditory cortex increased with increasing sequence variance along each perceptual dimension. The spatial extent, region, and laterality of the cortical regions most responsive to variations in pitch or timbre at the univariate level of analysis were largely overlapping. However, patterns of activation in response to pitch or timbre variations were discriminable in most subjects at an individual level using multivoxel pattern analysis, suggesting a distributed coding of the two dimensions bilaterally in human auditory cortex. Pitch and timbre are two crucial aspects of auditory perception. Pitch governs our perception of musical melodies and harmonies, and conveys both prosodic and (in tone languages) lexical information in speech. Brightness-an aspect of timbre or sound quality-allows us to distinguish different musical instruments and speech sounds. Frequency-mapping studies have revealed tonotopic organization in primary auditory cortex, but the use of pure tones or noise bands has precluded the possibility of dissociating pitch from brightness. Our results suggest a distributed code, with no clear anatomical distinctions between auditory cortical regions responsive to changes in either pitch or timbre, but also reveal a population code that can differentiate between changes in either dimension within the same cortical regions.